2010
DOI: 10.1080/13602004.2010.515823
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Sex Education among Muslim Adolescents in Canada

Abstract: The present study aims to explore the perceptions of Muslim adolescents in Canada regarding sex education offered to them by Canadian schools, their parents, and Islamic centers. Semi-structured interviews were conducted with nine Muslim adolescents from Asia, Africa, Europe and North America. The findings of the study reveal that despite the usefulness of sex education programs provided by Canadian schools, some of the contents of these programs were problematic for Muslim adolescents. The study also found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, this issue still causes a significant tension and lack of trust between health policymakers and religious leaders who believe that condom promotion will promote immorality and promiscuity (Barmania & Aljunid, 2016 ; Kamarulzaman, 2013 ). In Islamic communities, social norms expect sexual abstinence; virginity at the time of marriage remains a virtue, while sex outside marriage is considered sinful (Zain Al-Dien, 2010 ). However, recent studies among university students in some Islamic countries have shown that many students engage in pre-marital sex.…”
Section: Introductionmentioning
confidence: 99%
“…However, this issue still causes a significant tension and lack of trust between health policymakers and religious leaders who believe that condom promotion will promote immorality and promiscuity (Barmania & Aljunid, 2016 ; Kamarulzaman, 2013 ). In Islamic communities, social norms expect sexual abstinence; virginity at the time of marriage remains a virtue, while sex outside marriage is considered sinful (Zain Al-Dien, 2010 ). However, recent studies among university students in some Islamic countries have shown that many students engage in pre-marital sex.…”
Section: Introductionmentioning
confidence: 99%
“…All these study findings align with international technical guidelines that advocated for age-appropriate sexuality education across all levels of schooling (UNESCO, 2018). Viewed collectively, findings from this study should be used to challenge concerns that parents oppose the delivery of school-based sexuality education (Dyson, 2010;Robinson et al, 2017;UNESCO, 2018), even if the parents report a religious affiliation (Benedicta, 2010;Hashem, 2009;Tabatabaie, 2015;Zain Al-Dien, 2010). While the vast majority of parents agreed to the provision of school-based sexuality education, and to shared responsibility, it is important to highlight that about half the parents in this study were either not aware of any school-based education being delivered at their child's school or indicated that it had not been provided.…”
Section: Discussionmentioning
confidence: 95%
“…Another recent research has shown that low social support in older age has real societal cost in respect of living conditions, age, marital status, and health as associated factors (Dai et al, 2016). Many other researchers have found social support as a safeguard for stressful conditions of the old age period that can lead to depression (Dien-Zain, 2010;VanderHorst & Mclaren 2005;Cappeliez et al, 2005;Jang et al, 2005). Perceived functional SS is associated with depression.…”
Section: Introductionmentioning
confidence: 99%